Kebijakan Kantor Wilayah Kementerian Agama Provinsi Banten dalam Meningkatkan Profesionalisme Guru Madrasah Ibtidaiyah - Irmawanty Irmawanty; Mohammad Syarif Sumantri; Arita Marini; Yudi Juniardi (EduBasic Journal: Jurnal Pendidikan Dasar, 2019)
Education is one of the instruments of change and national civilization, especially related to human values and mental attitudes. The teacher is an activator, motivator and evaluator of education so that its existence must always be in a quality position. For that reason, it is necessary to conduct sustainable professionalism development as a form of optimizing the teachers’ role and function of in school or madrasah as formal institutions. By this ideal fuction, the authors see the spirit of optimism by educational world to encourage the formation of a fully prosperous civil society. This research investigated how the policy of the Regional Office of the Ministry of Religion of Banten Province in improving the professionalism of Madrasah Ibtidaiyah teachers. This research used a qualitative method by documentary studies based on reports on activities carried out by the Madrasah Education Division in 2018 and in depth-interviews to the Heads of Madrasah Education Division and the Section Heads of Madrasah Education Division. Based on the results of data analysis, this study concluded that the Regional Office of the Ministry of Religion of Banten Province has held three valuable programs related to enhance the teachers’ professionalism. They were strengthening the competence of Madrasah Ibtidaiyah teachers through various program and pedagogical activities, increasing managerial competence by several trainings and increasing teachers’ welfare through providing financial incentive, and conducting scientific competitions.